Molecular Epidemiology of Group A Rotavirus Diarrhea among Children in Buenos Aires, Argentina, from 1999 to 2003 and Emergence of the Infrequent Genotype G12 - Castello, Alejandro Andrés (2006)
To examine the epidemiology of rotaviruses in Buenos Aires, Argentina, we screened 1,212 stool samples from children with diarrhea in the southern district of Buenos Aires from 1999 to 2003. We identified 187 samples (15.4%) that were positive for group A rotavirus by use of antigen enzyme-linked immunosorbent assay. Among these specimens, 112 were available for typing: 93 (83.0%) were single-type infections, 9 (8.0%) were mixed-type infections with more than one G or P type, and 10 (8.9%) were G and/or P nontypeable. In contrast to the findings in our last study, from 1996 to 1998, genotype P[4], G2 strains were almost completely absent and P[8], G1 and P[8], G4 strains were dominant, representing more than 80% of the G and P types found. Genotypes G2 and G9 were detected in few samples, and type G3 was completely absent. We identified several uncommon genotype G12 strains, representing the first detections outside of Asia and the United States, by sequencing. Using a genotype G12-specific reverse transcription-PCR, we identified eight (6.7%) positive samples for the 1999 to 2003 period. The high degree of sequence identity between recent G12 isolates from Argentina, the United States, and Asian countries suggests a relatively recent introduction(s) of these strains into humans from a common progenitor. The Argentinean G12 strains belonged to genotype P[9], similar to most of the recently described Asian G12 strains. The finding of G12 strains in several other regions of the world raises the possibility that G12 may be emerging globally and suggests that surveillance for this strain should be conducted routinely.